Metabolic and Productive Response and Grazing Behavior of Lactating Dairy Cows Supplemented with High Moisture Maize or Cracked Wheat Grazing at Two Herbage Allowances in Spring - Verónica M. Merino; Lorena Leichtle; Oscar A. Balocchi; Francisco Lanuza; Julián Parga; Rémy Delagarde; Miguel Ruiz-Albarrán; M. Jordana Rivero; Rubén G. Pulido (Animals, 2021)
The aim was to determine the effect of the herbage allowance (HA) and supplement type (ST) on dry matter intake (DMI), milk production and composition, grazing behavior, rumen function, and blood metabolites of grazing dairy cows in the spring season. Experiment I: 64 Holstein Friesian dairy cows were distributed in a factorial design that tested two levels of daily HA (20 and 30 kg of dry matter (DM) per cow) and two ST (high moisture maize (HMM) and cracked wheat (CW)) distributed in two daily rations (3.5 kg DM/cow/day). Experiment II: four mid-lactation rumen cannulated cows, supplemented with either HMM or CW and managed with the two HAs, were distributed in a Latin square design of 4 × 4, for four 14-d periods to assess ruminal fermentation parameters. HA had no effect on milk production (averaging 23.6 kg/day) or milk fat and protein production (823 g/day and 800 g/day, respectively). Cows supplemented with CW had greater protein concentration (+1.2 g/kg). Herbage DMI averaged 14.17 kg DM/cow.day and total DMI averaged 17.67 kg DM/cow.day and did not differ between treatments. Grazing behavior activities (grazing, rumination, and idling times) and body condition score (BCS) were not affected by HA or ST. Milk and plasma urea concentration increased under the high HA (+0.68 mmol/L and +0.90 mmol/L, respectively). Cows supplemented with HMM had lower milk and plasma urea concentrations (0.72 mmol/L and 0.76 mmol/L less, respectively) and tended (p = 0.054) to have higher plasma β-hydroxybutyrate. Ruminal parameters did not differ between treatments.